Perception of Paediatric Dentists on Use of i-Grip vs Flossed Endodontic Files during Pulpectomy Procedures in Children: A Quasi-experimental Study - Ishani Ratnaparkhi; J Jasmin Winnier; Shilpa Naik; Sonal Tandel; Deepshikha Mehrotra; Divya Shetty (Journal of Clinical and Diagnostic Research)
Introduction: Mishaps such as the accidental ingestion of endodontic instruments and crowns may occur during dental treatment in children. Although such accidents are rare, they can be potentially harmful to patients. The use of a rubber dam is not always possible in paediatric dentistry; thus, the attachment of floss to endodontic files is commonly done during the pulpectomy procedure. However, there are some challenges associated with using Flossed Endodontic Files (FEFs). To overcome these difficulties, a system called i-Grip was introduced. Aim: To evaluate the perception and compare the ease, convenience and safety of i-Grip versus FEFs as perceived by Paediatric Dentists during pulpectomy procedures in children. Materials and Methods: A post-test quasi-experimental study was conducted in the Department of Paediatric and Preventive Dentistry, D.Y. Patil University, School of Dentistry, Navi Mumbai, Maharashtra, India, among 40 Paediatric Dentists over a period of three months. The Paediatric Dentists were asked to use the i-Grip for four weeks, after which they completed validated questionnaires. Statistical Package for the Social Sciences (SPSS) software version 23.0 was used for data analysis. The answers to the questions were statistically analysed using the Z-test of proportion. Results: The mean age of males were 35±0.743 years and females were 25.37±0.543 years. A total of 27 (67.5%) participants found placing the file in the i-Grip to be very easy. 22 (55%) found the i-Grip to be very convenient to use. 31 (77.5%) Paediatric Dentists found the i-Grip to be extremely safe, 6 (15%) considered it to be moderately safe and none found it to be extremely unsafe. There was a statistically significant difference between the ease, comfort and safety of i-Grip compared to FEF (p<0.05). Conclusion: Paediatric dentists reported that the i-Grip was easy to use, convenient and safe when compared to FEF. The i-Grip is an innovative safety tool that can be utilised in paediatric patients during pulpectomy procedures instead of FEF.